Advancements in anion exchange membrane electrolysers: from catalysts to life cycle assessment - Feriel Mustapha; Damien Guilbert; Bodo Gross (International Journal of Sustainable Energy)
Anion exchange membrane (AEM) water electrolysis is a promising technology for green hydrogen production from renewable energy sources (RES). Despite its many advantages, it is not yet mature enough to compete with proton exchange membrane (PEM) electrolysers in terms of current density and durability. This review examines the state-of-the-art AEM electrolysers, focusing on technical specifications, leading manufacturers, durability challenges, and recent market developments. Additionally, life cycle assessments highlight opportunities to reduce environmental impacts by minimising reliance on fluorinated polymers and improving recycling strategies. Furthermore, this study emphasises the importance of optimising both hydrogen and oxygen evolution reactions to enhance performance. Finally, a comprehensive SWOT analysis underscores AEM's strengths, including low costs and compatibility with RES, while identifying innovation opportunities. Although AEM electrolysers provide a viable pathway for decarbonisation, overcoming technical and economic barriers is crucial for their large-scale adoption.